ijsr 2021
DOI: 10.36106/ijsr/6428606
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Attachment Styles on Marital Satisfaction Among Married Couples

Abstract: Researchers are interested in marital satisfaction since it is signicant for couples' psychological well-being. They have been studying the factors that lead to a happy marriage for a long time. Adult attachment styles, according to the prior study, serve an active role in forming an intimate relationship. The purpose of the current study was to examine the inuence of adult attachment styles (Secure, Fearful, Dismissive, and Preoccupied) on marital satisfaction among Indian married couples. 304 respondents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
4
0
4
Order By: Relevance
“…Interactions that previously responded to Christensen et al found that by giving behavioral couples therapy, emotional reactions or negative responses from interactions that cause problems in communication are found to be overcome by couples in the long term [40]. In communication skill training couples who can maintain communication skills, the quality of the relationship or satisfaction in the relationship is found to increase [41]. Changes in more effective communication and more positive behavior from behavior exchange as well as reduced negative impacts such as avoiding each other, distancing and fighting make the assessment between husband and wife more positive and relationship satisfaction gradually increases.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions that previously responded to Christensen et al found that by giving behavioral couples therapy, emotional reactions or negative responses from interactions that cause problems in communication are found to be overcome by couples in the long term [40]. In communication skill training couples who can maintain communication skills, the quality of the relationship or satisfaction in the relationship is found to increase [41]. Changes in more effective communication and more positive behavior from behavior exchange as well as reduced negative impacts such as avoiding each other, distancing and fighting make the assessment between husband and wife more positive and relationship satisfaction gradually increases.…”
Section: Discussionmentioning
confidence: 99%
“…Taking part in such training by married women reduced stress in the marital dyad, increased their satisfaction in marriage and reduced burnout (Amini et al, 2016;Sirin et al, 2016). During communication programs, participants develop skills such as empathy, conversation, conflict resolution, which has been significantly associated with greater marital satisfaction (Askari, Mohd Noah, Aishah Bt Hassan, Bt Baba, 2013;Haris, Kumar, 2018) leading to less burnout (Nejatian et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Marital satisfaction ini juga erat kaitannya dengan kesehatan mental pasangan yang menjalani hubungan pernikahan. Marital satisfaction merupakan pengalaman dan penilaian subjektif (Haris & Kumar, 2018). Selain itu, marital satisfaction juga dapat dikatakan sebagai penilaian seseorang terhadap hubungan pernikahan yang dijalani, seseorang merasa senang atau tidak dalam hubungan tersebut (Roach, Frazier, & Bowden, 1981).…”
Section: Marital Satisfactionunclassified
“…Hal ini karena selain membuat pasangan bertahan dalam hubungan pernikahan, marital satisfaction juga menjadi salah satu faktor yang mempengaruhi perkembangan anak (Kwan, Kwok, & Ling, 2015). Bagi perempuan, kepuasan pernikahan berasal dari hubungan yang harmonis (intim) dan kasih sayang yang diberikan pasangan (Haris & Kumar, 2018). Kondisi itu dapat mengurangi stress yang mungkin terjadi pada perempuan yang disebabkan karena pengasuhan anak (Kwan, Kwok, & Ling, 2015).…”
Section: Marital Satisfactionunclassified